The Fate of Periprosthetic Joint Infection Following Megaprosthesis Reconstruction. Issue 4 (11th October 2021) - Sukhonthamarn, Kamolsak; Tan, Timothy L.; Strony, John; Brown, Scot; Nazarian, David; Parvizi, Javad
Abstract : Background: A megaprosthesis may be used for reconstruction in patients with massive bone loss or a periprosthetic fracture. Periprosthetic joint infection (PJI) may occur after a megaprosthesis reconstruction and may pose a major challenge. The outcomes of managing PJI in patients with a megaprosthesis is relatively unclear. The aim of this study was to investigate the clinical course and outcomes of PJI in patients with a megaprosthesis in place. Methods: From a total of 219 patients who underwent megaprosthesis replacement for non-oncologic conditions, 38 (17.4%) developed subsequent PJI. A retrospective review of the medical record was performed to ascertain the course of the PJI and treatment outcomes. Kaplan-Meier analysis was performed to evaluate the survival function, and the log-rank test was used to assess differences in outcome measures. Results: The surgical management of 33 patients with PJI included debridement, antibiotics, and implant retention (DAIR) (82%), consisting of DAIR with modular component exchange (19 patients) and DAIR without component exchange (8 patients); 2-stage exchange arthroplasty (9%); resection arthroplasty (6%); and a single-stage revision arthroplasty (3%). The Kaplan-Meier survivorship analysis demonstrated that the overall survival rate was 65.1% at 2 years. The mortality rate was 15%, with many patients undergoing salvage procedures including amputation (18%), arthrodesis (6%), and resection arthroplasty (6%). Conclusions: The rate of PJI after megaprosthesis reconstruction, 17% in this study, appears to be very high. The management of PJI in these patients is challenging, with 1 of 3 patients undergoing failed treatment. Despite the limited options available, DAIR seems to be an appropriate treatment strategy for some of these patients. Further data on a larger cohort are needed to assess the success of various surgical procedures and predictors of failure in this challenging patient population. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.